(untitled) (Russian Medical and Social Journal, 2019)
Introduction:According to the information of Ministry of Health of the Russian Federation 12532 people died of prostate cancer in 2016.Detectability of the prostate cancer is increased over the past few years. It is discovered at earlier stages.Today the best practice of treatment a localized prostate cancer is the radical retropubic prostatectomy. The main method for prevention of postsurgical vesicourethral anastomosis stricture is the formation of sealed anastomosis with a exact comparison of mucous membranes without tissue tension. Purpose of the study: to investigate the early and long-term outcomes of the use of new technology on the number of postoperative strictures of the proximal urethra. Objective: to conduct a comparative study of the effect of intraluminal and non-intraluminal sutures in the vesicourethral anastomosis on the risk of postoperative vesicourethral strictures. Patients and Methods:We have performed 126 radical retropubic prostatectomies from January 2016 to December 2016.Patients are splitted in two groups. In the first group (87 patients) intraoperative vesicourethral anastomosis was performed according to classical scheme with intraluminal sutures.In the second group (39 patients) anastomosis was formed without mucous.When you put a cystourethral anastomosis operating a prostate cancer during a radical retropubic prostatectomy, it is appropriate to use suture without mucous. In our medical center formation of vesicourethral anastomosis is performed with Bicril 3/0 thread.For all patiens 5 ligatures were applied on anstomosis.Anasomosis leakage was checked by filling urinary bladder with 100 ml.All patients were examinated in 3, 6 and 9 months after the operation.The examination included computer tomography of the chest, abdomen and pelvis with contrast, transrectal ultrasonography, ultrasonography of the urinary bladder (to measure residual urine) and uroflowmetry. If the urination rate was below 15 ml/s, retrograde urethrography was performed. Main outcomesUrethral drainage was performed during 10.3 ± 3 days in the first group and during 9.9 ± 3 days in the second group.Vesicourethral anastomosis stricture was observed in 22 (25.2¬%) cases in the first group and in 6 (15.3%) cases in the second group. Сonclusions: This method allows one to avoid the eversion of the urinary bladder which decreases the operation time and probability of the bladder neck injury.